2013
DOI: 10.1371/journal.pone.0074175
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Mir-144-ZFX Pathway in Growth Regulation of Non-Small-Cell Lung Cancer

Abstract: BackgroundLung cancer is the leading cause of cancer-related death worldwide. Non-small cell lung carcinoma (NSCLC) accounts for most of the lung cancer cases and the prognosis of this disease remains poor despite decades of intensive investigation. Thus new insights into underlying mechanisms by which NSCLC develops are avidly needed as the basis for development of new lines of therapeutic strategies. The past decade has witnessed a growing interest on the regulatory roles of micro RNAs on various categories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 45 publications
1
52
0
Order By: Relevance
“…Results of the present study are consistent with the results of previous studies on liver cancer and non-small cell lung cancer (34,35). It is generally considered that miR-144 is able to function as a suppressor gene of tumor proliferation and affect the prognosis of patients with osteosarcoma (36,37).…”
Section: Discussionsupporting
confidence: 92%
“…Results of the present study are consistent with the results of previous studies on liver cancer and non-small cell lung cancer (34,35). It is generally considered that miR-144 is able to function as a suppressor gene of tumor proliferation and affect the prognosis of patients with osteosarcoma (36,37).…”
Section: Discussionsupporting
confidence: 92%
“…ZFX overexpression has been observed in variant types of cancer including human laryngeal SCC (LSCC) (12), prostate (13) and gastric cancer (14-16), human gliomas (17,18), non-small cell lung cancer (NSCLC) (19) and breast cancer (20). Consistent with these studies, here we showed that ZFX, a protein involved in survival and self-renewal of embryonic stem cells and implicated in the development of multiple types of cancer, was overexpressed in the tongue SCC samples.…”
Section: Discussionmentioning
confidence: 99%
“…miR-144 was originally identified as an erythroid-specific miRNA required for the survival and maturation of erythroid lineage (14,15). Ample studies have also revealed important roles for miR-144 in tumorigenesis and cancer treatment (16). In different types of cancers, downregulation of miR-144 has been observed, such as osteosarcoma and mesothelioma, indicating that miR-144 may be a potential tumor suppressor (17,18).…”
Section: Introductionmentioning
confidence: 99%